Household food insecurity, sociodemographic and lifestyle risk factors associated with high blood pressure among women in farming communities in Ghana - Aaron Kobina Christian; Ruth Tenkoramaa Owu; Irene A. Kretchy (BMC Women's Health)
Abstract Background Hypertension remains a primary contributor to avoidable mortality and impairment. This study aimed to examine the association between household food insecurity (HFI), another public health concern, and hypertension among women farmers in peri-urban and rural communities in Ghana. Methods Self-reported hypertension status, blood pressure measurement, and HFI were assessed using data on 430 women from a cross-sectional survey. We examined the odds of hypertension in women experiencing different categories of food insecurity while controlling for other known factors. Results Close to 74% (n = 319) of respondents belonged to households that were food-secure with 26% (n = 111) in food-insecure households. At the time of the survey, about a fifth of the participants (19%) reported to have ever been diagnosed with hypertension and 22% were living with high blood pressure (i.e., systolic: 140 mm Hg or higher and diastolic: 90 mm Hg or higher). Living in a rural community compared to a peri-urban community was associated with lower odds of living with high blood pressure. Older women were more likely than younger women to report having known hypertension and living with high blood pressure. Dangbe women were less likely to have high blood pressure than women from other ethnic groups. An increase in physical/morbidity activity was associated with a decreased likelihood of high blood pressure among food-insecure women. Conclusions This study buttresses the importance of hypertension awareness among older women, particularly, in urbanizing communities, and the need to explore mediating factors through which ethnicity may influence living with high blood pressure.